2015
DOI: 10.1111/geb.12304
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of climate, stand variables and liana abundance for carbon storage in tropical forests

Abstract: Aim To develop an integrative framework to evaluate variation in aboveground carbon storage (AGC). A model that can be applied to understand and predict how global‐change drivers influence tropical carbon sinks. Location Old‐growth tropical forests world‐wide. Methods Using structural equation modelling (SEM), we propose an a priori model to evaluate the direct and indirect effects of climate, stand variables (basal area, tree diameter and wood density at plot level) and liana abundance on AGC. Our model indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 46 publications
(169 reference statements)
0
40
1
Order By: Relevance
“…; Durán et al . ). There are four good reasons why lianas are more successful than trees in these conditions.…”
Section: Discussionmentioning
confidence: 97%
“…; Durán et al . ). There are four good reasons why lianas are more successful than trees in these conditions.…”
Section: Discussionmentioning
confidence: 97%
“…A 3 year liana removal experiment in a humid lowland Panamanian forest found an overall increased in woody biomass following liana removal, with woody stems going from 29% to 44% of aboveground biomass when lianas were absent [ van der Heijden et al ., ]. A recent model simulation also indicated that rising temperatures and increased dryness favored liana growth, with an overall negative effect on aboveground forest C storage [ Duran et al ., ]. Thus, reductions in tree biomass in favor of other life forms may reduce aboveground C storage in tropical forests with climate change.…”
Section: Review Of Global Change Effects On Tropical Ecosystemsmentioning
confidence: 99%
“…The relationship between biodiversity and carbon storage is being debated as one of the current ecological topics (Cavanaugh et al, 2014;Day, Baldauf, Rutishauser, & Sunderland, 2014;Ruiz-Benito et al, 2014;Ruiz-Jaen & Potvin, 2011), and some aspects of climate-related effects have been well investigated (Durán, Sánchez-Azofeifa, Rios, & Gianoli, 2015;Wu et al, 2015). Because biomass is an important component of forest stand productivity, the relationship between biomass carbon and biodiversity can also be assimilated to the one of biodiversity and ecosystem function (Lasky et al, 2014).…”
Section: Introductionmentioning
confidence: 99%